The Sustainability Of Malay Traditional Craftsmanship As A Tourism Product In Melaka - Abd Hamid, Nor Fatimah (2017)
Cultural heritage as a tourism product has motivated many local and international tourists to spend time at a tourism destination. Cultural heritage encompasses of tangible and intangible heritage. However, the development of cultural heritage as a tourism product has mainly concentrated on tangible heritage. Despite the fact that, craft as an element in traditional craftsmanship is seen as intangible cultural heritage which has become as a tourism product in a certain tourism destination. However, a lack of attention has been given to the skill and knowledge of these craftsmen who has produced the crafts.